Glomangioma of the hip - (:unkn) unknown (BLACKWELL PUBLISHING INC, 2003)
Background. Glomus tumors may occur in any region of the body, but they are very rare in the hip. Objective. To present the eighth reported case of a glomus tumor of the hip up to date. Methods. This is a case report and a literature review. Results. A 68-year-old man presented with severe pain and tenderness in the right hip, especially on palpation and in the sitting position. On physical examination, there was a soft palpable subcutaneous mass and severe tenderness in the right hip. Ultrasound revealed a hypervascular subdermal mass that was 2 cm in diameter. The lesion arose from the dermis and extended into the subcutaneous tissue. It was totally excised under local anesthesia. The histopathologic diagnosis was a glomangioma. The patient has been symptom free in the 2 months of follow-up. Conclusions. Glomus tumors should be kept in mind in the differential diagnosis of painful subdermal mass. Surgical excision of the lesion with a sufficient margin of surrounding normal tissue not only achieves the exact diagnosis but also results in adequate treatment. In case of the presence of malignant features, a wide excision is needed with a close follow-up of patient for regional or distant metastases.
Keywords: GLOMUS TUMOR; NERVE; PAIN